2018
DOI: 10.1080/10428194.2018.1473573
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of BCR-ABL1 kinase domain mutations in chronic myeloid leukemia patients with resistance to tyrosine kinase inhibitors

Abstract: Tyrosine kinase inhibitor (TKI) therapy is the current treatment of choice for patients with chronic phase chronic myeloid leukemia (CML) leading to rapid and durable hematological as well as molecular responses. However, emergence of resistance to TKIs has been the major obstacle to treatment success on long term. In this regard kinase domain mutations are the most common mechanism of therapy failure. In this study, we analyzed peripheral blood samples from 17 CML patients who had developed resistance to vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The so-called “myeloid panels” include the ABL1 exons coding for the KD, but DNA-based mutation screening would mainly have untranslocated ABL1 as a substrate, thus dangerously “diluting” mutations down to a level that might be undetectable even by NGS. Some studies have reported the setup and application of in-house-developed protocols for BCR-ABL1 KD mutations screening implemented on different NGS platforms [2931, 34, 35, 38, 6062].…”
Section: Resultsmentioning
confidence: 99%
“…The so-called “myeloid panels” include the ABL1 exons coding for the KD, but DNA-based mutation screening would mainly have untranslocated ABL1 as a substrate, thus dangerously “diluting” mutations down to a level that might be undetectable even by NGS. Some studies have reported the setup and application of in-house-developed protocols for BCR-ABL1 KD mutations screening implemented on different NGS platforms [2931, 34, 35, 38, 6062].…”
Section: Resultsmentioning
confidence: 99%
“…This is especially important for BCR‐ABL1 KD mutation monitoring, regardless of sequencing platform, due to transcript amplification (Potapov & Ong, ). For this reason, previous studies, which used the Roche NGS platform, suggested setting the VAF limit between 1% and 5% (Machova Polakova et al ., ; Soverini et al ., ; Erbilgin et al ., ). In our study, we adopted Q5 polymerase (New England Biolabs, Ipswich, MA, USA) for amplification of BCR‐ABL1 KD, which is currently the most accurate PCR polymerase (280 times more accurate than “reference” Taq polymerase) (Potapov & Ong, ).…”
Section: Discussionmentioning
confidence: 99%
“…Next‐generation sequencing (NGS) as an alternative method can provide enhanced sensitivity and earlier mutation detection. The NGS platform used most frequently for BCR‐ABL1 KD sequencing is 454 from Roche (Basel, Switzerland) (Machova Polakova et al ., ; Baer et al ., ; Soverini et al ., ; Erbilgin et al ., ). The use of Ion Torrent (Thermo Fisher Scientific, Waltham, MA, USA) technology and the widely implemented Illumina (San Diego, CA, USA) platform has been reported by fewer authors to date (Eyal et al ., ; Deininger et al ., ; Kizilors et al ., ).…”
mentioning
confidence: 99%
“…The identification of BCR-ABL1 as the major driver in the pathogenesis of CML led to the development of targeted therapies with ABL1 tyrosine kinase inhibitors (TKIs) such as Imatinib, Dasatinib, and Ponatinib [58,59]. Treatments with TKIs in the initial chronic phase of CML have been shown to induce remarkable haematological and cytogenetic responses, however, treatments of advanced stage patients or individuals with ABL1 kinase domain mutations are much more challenging and most importantly, none of these monotherapies are curative [60,61,62]. Strong evidence indicates that LSCs, including quiescent LSCs, are insensitive to TKIs and constitute a critical source of leukemia recurrence and a significant reservoir for the emergence of TKI-resistant sub-clones, necessitating lifelong treatment for most patients [57,63,64,65,66,67,68,69,70].…”
Section: Autophagy Plays Context-dependent Roles In Leukemia Initimentioning
confidence: 99%